"Talkin 'bout my generation". Urbane Zeitlichkeiten und Generationenforschung. - Fuhg, Felix (Deutsches Institut für Urbanistik, 2021)
Dieser Artikel zeigt anhand ausgewählter Beispiele aus der Jugendgeschichte Londons in der Nachkriegszeit, wo sich in der Auseinandersetzung mit einer sich wandelnden Stadt Verschränkungen von Generationalität und Zeitdiskursen offenbarten. Bis heute wird im kollektiven popkulturellen Gedächtnis eine generationelle Revolte mit dem kulturellen Leben in der britischen Hauptstadt Mitte der 1960er Jahre assoziiert.

City life, temporal notions of the urban as well as generational identities and general readings of historical change: these three research fields have been widely researched in the previous years, but their crossroads never stood in the centre of historical research. With the help of the case studies coming of London’s post-war youth history, this contribution identifies fruitful intersections of research on city life, urban temporal notions and the generational reading of urban change and transformation. Therefore, the article illustrates how generational identities have been associated with the changing temporal pattern of city life. It argues that changing temporal rhythms of the urban contributed to generational fragmentation and notions of a generational “self” in history.
Keywords: Großstadt; Stadtgeschichte; Kulturgeschichte; Jugend; Urbanität; Jugendlicher; Alltagskultur; Massenkultur; Generationskonflikt; Sechziger Jahre; Nachkriegszeit; Stadtentwicklung; Geschwindigkeit; Jugendkultur; Popkultur